Pica in Individuals with Developmental Disabilities - Sturmey, Peter; Williams, Don E. (Autism and child psychopathology series,, 2016)
This book provides a comprehensive overview of the clinical phenomenon of pica. It focuses specifically on the disorder as it presents in children, adolescents, and adults with autism spectrum disorder (ASD) and intellectual disabilities (ID). Initial chapters introduce current theories and definitions, followed by a more detailed examination of how developmental disabilities complicate diagnosis and intervention. The volume describes evidence-based and clinically sound approaches to the treatment and prevention of pica in school and adult clinical settings, ranging from behavioral treatment to function-based interventions. In addition, it discusses common diagnostic, client, and provider issues that result in pica remaining undetected among individuals with ASD and ID. Featured topics include: Definition of pica in accessible terms, differentiating between various forms of the disorder. Issues and practical methods of prevention and treatment of pica in developmentally disabled persons. Functional and behavioral assessment methods for pica in individuals with ASD and ID. A range of effective behavioral and nonbehavioral treatments for pica. Illustrative cases and service delivery challenges. Areas for future research and practice. Pica in Individuals with Developmental Disabilities is an invaluable resource for researchers, clinicians and other professionals, and graduate students in clinical child and school psychology, behavior analysis/therapy, and social work as well as child and adolescent psychiatry, pediatrics, family studies, and special education.